Pendampingan Kegiatan PERJUSA (Perkemahan Jumat Sabtu) Sebagai Penguatan Karakter Kedisiplinan dan Kepemimpinan Peserta Didik SMK Teknologi Kotawaringin - Moh. Khoiri; Moh. Imam (Jurnal Pendidikan dan Pengabdian Masyarakat, 2026)
The Scout Movement continues to serve as a means of character development for the younger generation, particularly in fostering discipline and leadership among vocational school students. Discipline and leadership can be strengthened through mentoring during camping activities. The aim of this mentoring is to strengthen the discipline and leadership of Year 10 and Year 11 vocational school students through the Friday–Saturday camping programme (PERJUSA). The implementation of the programme consists of a preparation stage, an implementation stage, and an evaluation stage. Data collection techniques included documentation and observation during the implementation phase. The results of the PERJUSA mentoring programme indicate that the discipline and leadership traits of vocational school students were rated as good. The recommendation arising from this mentoring programme is that schools should establish structured scheduling, supervision and monitoring in the running of the Scouting extracurricular activity.